2020
DOI: 10.1021/acs.organomet.0c00315
|View full text |Cite
|
Sign up to set email alerts
|

Metallacarborane Assemblies as Effective Antimicrobial Agents, Including a Highly Potent Anti-MRSA Agent

Abstract: omeroD ssel nd wrtinezEwedinD wrgrit nd gmpru¡ %EpontD grl nd fennourD snes nd worenoD hvid nd wrt¡ %nezEwrt¡ %nezD vuis nd eixidorD prnes nd poxD wrk eF nd i£ nsD glr @PHPHA 9wetllrorne ssemlies s e'etive ntimiroil gentsD inluding highly potent ntiEwe gentF9D yrgnometllisFD QW @PQAF ppF RPSQERPTRF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Based on these results, COSAN.Na can therefore be declared a more stable antimicrobial agent than TET. As for MIC determination of COSAN.Na, the concentration range of MIC 80 confirmed in our study corresponds to the results of MIC (1–16 µg/mL) of the four derivatives of COSAN - described by Romero et al [ 46 ]. The researchers also stated that COSAN - derivatives possess bactericidal rather than bacteriostatic action towards E. faecalis and S. aureus .…”
Section: Discussionsupporting
confidence: 89%
“…Based on these results, COSAN.Na can therefore be declared a more stable antimicrobial agent than TET. As for MIC determination of COSAN.Na, the concentration range of MIC 80 confirmed in our study corresponds to the results of MIC (1–16 µg/mL) of the four derivatives of COSAN - described by Romero et al [ 46 ]. The researchers also stated that COSAN - derivatives possess bactericidal rather than bacteriostatic action towards E. faecalis and S. aureus .…”
Section: Discussionsupporting
confidence: 89%
“…The minimum bactericidal concentration (MBC) values indicated that these compounds had a bactericidal/fungicidal effect, since the ratio MBC/MIC was ≤2. However, while previously tested [ 1 ] − derivatives with a cisoid conformation were highly effective against Gram-positives, 53 a ,54 the parent metallabis(dicarbollides) studied here had a reduced antimicrobial effect towards this group of bacteria, but increased potency against Gram-negative and Candida species.…”
Section: Resultsmentioning
confidence: 63%
“…Clinical bacterial ( N = 9) and yeast ( N = 3) isolates previously tested for susceptibility to other metallacarborane compounds were used here. 54 As Gram-negative bacteria, three strains of Escherichia coli and two of Pseudomonas aeruginosa were tested, including strains that are susceptible to commonly used antimicrobials ( E. coli 190940 and P. aeruginosa 190089) or are multidrug resistant ( E. coli BLEE 192348, E. coli LF82 and P. aeruginosa IMI 187182). As Gram-positive bacteria, we tested two Enterococcus faecalis strains ( E. faecalis 190093 and E. faecalis 194844), and two of Staphylococcus aureus ( S. aureus MRSA 182851, which is multidrug-resistant, and S. aureus 180895).…”
Section: Methodsmentioning
confidence: 99%
“…[27][28][29] All these characteristic make COSAN and derivatives promising pharmacophores for biomedical applications, [30][31][32] among them for cancer therapy, [33,34] or as antimicrobial agents. [35] On the other hand, another remarkable anionic boron clusters is the closo-dodecaborate dianion, [B 12 H 12 ] 2À , and derivatives, [36] which have also demonstrate to have high chemical stability and hydrolytic capacity especially for their sodium salts, [37][38][39] which along with the low toxicity, [40] make them ideal candidates to design pharmacophores. [41][42][43][44] Despite the enormous advance of highly emissive carborane-based compounds over the past decades, the development of luminescent systems bearing anionic boron clusters, in especial COSAN and closo-dodecaborate, has been very limited, [45] and only a few examples reported by us [46][47][48][49] and others [50][51][52] are known.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, radiolabeling COSAN with an appropriate radioisotope ( 124 I) leads to suitable theragnostic agents for in vivo visualization by Positron Emission Tomography (PET) and boron carriers for boron neutron capture therapy (BNCT) [27–29] . All these characteristic make COSAN and derivatives promising pharmacophores for biomedical applications, [30–32] among them for cancer therapy, [33,34] or as antimicrobial agents [35] …”
Section: Introductionmentioning
confidence: 99%